2017
DOI: 10.2298/vsp150716107v
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis-related knowledge among Serbian postmenopausal women

Abstract: Background/Aim. Osteoporosis mainly affects women in the early years following menopause. The aim of this study was to determine the level of knowledge about osteoporosis and osteoporosis related risk factors in postmenopausal women in Serbia. Methods. The study included postmenopausal women regardless if suffering from osteoporosis or not. Assessment of knowledge was carried out by using the Osteoporosis Knowledge Assessment Tool -Shorter Version (OKAT-S) questionnaire that was validated for Serbian populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
0
6
0
2
Order By: Relevance
“…A recent study by Serbia 18 found that out of 132 postmenopausal women, about 59% had normal BMD, whereas 41% had osteoporosis or osteopenia. The study revealed that about one-third of the patients had a fracture, and the average number of fractures was 1.47 in all the women in the study.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…A recent study by Serbia 18 found that out of 132 postmenopausal women, about 59% had normal BMD, whereas 41% had osteoporosis or osteopenia. The study revealed that about one-third of the patients had a fracture, and the average number of fractures was 1.47 in all the women in the study.…”
Section: Introductionmentioning
confidence: 97%
“…There has been extensive research on osteoporosis and osteopenia in Serbia. 18 21 However, to the best of our knowledge, none of these studies has assessed the fracture risk factors associated with these two conditions, and a standardized FRAX questionnaire was not routinely applied in such assessments.…”
Section: Introductionmentioning
confidence: 99%
“…Udeo tačnih odgovora na pitanja iz upitnika je bio od 27,94-74,26% a prosečni OKAT-S skor je bio oko polovine od maksimalno mogućeg rezultata. 5 Slične studije u svetu su, za razliku od naših prilika, veoma brojne i uključile su raznovrsne subpopulacije stanovništva kao što su adolescenti i osobe mladjeg uzrasta, žene i muškarce srednje životne dobi kao i zdravstvene profesionalce -lekare i medicinske sestre. [6][7][8][9] Zato je cilj ove studije bio da korišćenjem validnog instrumenta procene kod žena u postmenopauzi ustanovi stepen znanja o značaju, merama prevencije i terapiji osteporoze u našoj sredini.…”
Section: Originalni Naučni Rad / Original Scientific Article Uvodunclassified
“…Rezultati našeg istraživanja su vrlo slični prethodno publikovanim rezultatima iz jedne od raritentnih studije koja je sprovedena kod nas. 5 Kombinovanjem podataka našeg i tog istraživanja zaključuje se da oko 8-12% žena naše populacije starijih od 50 godina ima pogrešna odnosno netačna saznanja i stavove o osteoporozi što je podatak koji treba da zabrine i inicira dodatna istraživanja u ovoj oblasti i više, edukativne mere usmerene ka javnosti.…”
Section: Diskusijaunclassified
“…The central component of effective educational intervention by healthcare practitioners is awareness of the disease and the extent to which they practise preventive behaviour (Vujasinovic-Stupar et al, 2017). There is a shortage of evidence in industrialised and developing countries on women's awareness and practise of osteoporosis and preventive measures.…”
Section: Introductionmentioning
confidence: 99%